Idiopathic Internal Jugular Vein and Subclavian Vein Thrombosis: A Rare Case Report - Agrawal, Ankit (Cureus, 2019)
Venous thrombosis is a vascular disorder which is a consequence of Virchow’s triad: hypercoagulability, venous stasis, and endothelial injury. While lower extremity deep venous thrombosis is common, upper torso thrombosis is a rare clinical condition and usually a complication of central venous catheterization or malignancy-related paraneoplastic syndromes. Herein, we present a rare case of a 64-year-old male who presented with right upper extremity and right facial swelling who was found to have a thrombus in the right internal jugular vein and right subclavian vein with no predisposing factors. He was successfully treated with anticoagulation without any complications.